2018
DOI: 10.5539/jas.v11n1p546
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Insecticides Against Adult Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) on Cassava

Abstract: In this study, the effects of various chemical and biological insecticides on adults of the parasitoid species Trichogramma pretiosum (Riley) were examined in cassava. The chemical insecticides zeta-cypermethrin, lufenuron + profenofós, imidacloprid, thiamethoxam, and teflubenzuron and the biological agents Bacillus thuringiensis and Baculovirus erinnyis were evaluated. For each treatment group, the effects were evaluated using T. pretiosum mortality rates, longevity of females, the number of eggs p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Previous research has shown that confirmed fungus-related mortality depends on the virulence of fungal strains, EF species, Trichogramma species, and the application period (pre- or post-parasitism) [ 22 , 27 , 39 ]. Furthermore, the interactions between the EF and Trichogramma species were minimal for all biological parameters considered in this study, especially when compared with chemical insecticides [ 11 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that confirmed fungus-related mortality depends on the virulence of fungal strains, EF species, Trichogramma species, and the application period (pre- or post-parasitism) [ 22 , 27 , 39 ]. Furthermore, the interactions between the EF and Trichogramma species were minimal for all biological parameters considered in this study, especially when compared with chemical insecticides [ 11 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they are involved in pest control programs for over 200 insect species [8]. In particular, members of the Trichogrammatidae family have considerable potential as cost-effective control agents against Lepidoptera pests due to their ability to be easily mass-produced [8][9][10][11][12]. However, the use of non-selective pesticides in agricultural production systems limits the successful implementation of biological control programs that use Trichogrammatidae species due to the sensitivity of these organisms [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural enemies are important in pest control in planted forests, justifying the search for compatible microbial and chemical products 18 . The mycoinsecticides and chemical insecticides must have selectivity to the pest natural enemies 19,20 in order to maintain the effectiveness of the combined use of these methods.…”
mentioning
confidence: 99%
“…The best way to reduce their population to a noneconomic-injury level is through a combination of control methods, as in Integrated Pest Management (IPM). It is important to guarantee that the control methods, when used together, do not compromise the effectiveness of each other(Oliveira et al 2013, Torres and Bueno 2018, Feltrin- Campos et al 2019. Therefore, an important step for integrating biological and chemical control is the evaluation of the pesticide selectivity.…”
mentioning
confidence: 99%